At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Alright, let's tackle the summation problem step by step.
Given the expression:
[tex]\[ 3 \sum_{k=1}^n (2k - 3) + \sum_{k=1}^n (4 - 5k) \][/tex]
where [tex]\( n = 6 \)[/tex].
### Step 1: Calculate the First Summation Component
First, we consider the summation inside the first term:
[tex]\[ \sum_{k=1}^n (2k - 3) \][/tex]
Substitute [tex]\( n = 6 \)[/tex]:
[tex]\[ \sum_{k=1}^6 (2k - 3) \][/tex]
Calculate each term inside the summation for [tex]\( k = 1, 2, 3, 4, 5, 6 \)[/tex]:
- When [tex]\( k = 1 \)[/tex]: [tex]\( 2 \cdot 1 - 3 = -1 \)[/tex]
- When [tex]\( k = 2 \)[/tex]: [tex]\( 2 \cdot 2 - 3 = 1 \)[/tex]
- When [tex]\( k = 3 \)[/tex]: [tex]\( 2 \cdot 3 - 3 = 3 \)[/tex]
- When [tex]\( k = 4 \)[/tex]: [tex]\( 2 \cdot 4 - 3 = 5 \)[/tex]
- When [tex]\( k = 5 \)[/tex]: [tex]\( 2 \cdot 5 - 3 = 7 \)[/tex]
- When [tex]\( k = 6 \)[/tex]: [tex]\( 2 \cdot 6 - 3 = 9 \)[/tex]
Now add these values together:
[tex]\[ -1 + 1 + 3 + 5 + 7 + 9 = 24 \][/tex]
Thus, the first summation component is:
[tex]\[ \sum_{k=1}^6 (2k - 3) = 24 \][/tex]
Multiplying this by 3 gives:
[tex]\[ 3 \sum_{k=1}^6 (2k - 3) = 3 \cdot 24 = 72 \][/tex]
### Step 2: Calculate the Second Summation Component
Next, we consider the second summation:
[tex]\[ \sum_{k=1}^n (4 - 5k) \][/tex]
Substitute [tex]\( n = 6 \)[/tex]:
[tex]\[ \sum_{k=1}^6 (4 - 5k) \][/tex]
Calculate each term inside the summation for [tex]\( k = 1, 2, 3, 4, 5, 6 \)[/tex]:
- When [tex]\( k = 1 \)[/tex]: [tex]\( 4 - 5 \cdot 1 = -1 \)[/tex]
- When [tex]\( k = 2 \)[/tex]: [tex]\( 4 - 5 \cdot 2 = -6 \)[/tex]
- When [tex]\( k = 3 \)[/tex]: [tex]\( 4 - 5 \cdot 3 = -11 \)[/tex]
- When [tex]\( k = 4 \)[/tex]: [tex]\( 4 - 5 \cdot 4 = -16 \)[/tex]
- When [tex]\( k = 5 \)[/tex]: [tex]\( 4 - 5 \cdot 5 = -21 \)[/tex]
- When [tex]\( k = 6 \)[/tex]: [tex]\( 4 - 5 \cdot 6 = -26 \)[/tex]
Now add these values together:
[tex]\[ -1 + (-6) + (-11) + (-16) + (-21) + (-26) = -81 \][/tex]
Thus, the second summation component is:
[tex]\[ \sum_{k=1}^6 (4 - 5k) = -81 \][/tex]
### Step 3: Combine Both Summation Components
Finally, we combine the results of both summations:
[tex]\[ 3 \sum_{k=1}^6 (2k - 3) + \sum_{k=1}^6 (4 - 5k) = 72 + (-81) = -9 \][/tex]
### Final Answer
So, the value of the given summation when [tex]\( n = 6 \)[/tex] is:
[tex]\[ -9 \][/tex]
Given the expression:
[tex]\[ 3 \sum_{k=1}^n (2k - 3) + \sum_{k=1}^n (4 - 5k) \][/tex]
where [tex]\( n = 6 \)[/tex].
### Step 1: Calculate the First Summation Component
First, we consider the summation inside the first term:
[tex]\[ \sum_{k=1}^n (2k - 3) \][/tex]
Substitute [tex]\( n = 6 \)[/tex]:
[tex]\[ \sum_{k=1}^6 (2k - 3) \][/tex]
Calculate each term inside the summation for [tex]\( k = 1, 2, 3, 4, 5, 6 \)[/tex]:
- When [tex]\( k = 1 \)[/tex]: [tex]\( 2 \cdot 1 - 3 = -1 \)[/tex]
- When [tex]\( k = 2 \)[/tex]: [tex]\( 2 \cdot 2 - 3 = 1 \)[/tex]
- When [tex]\( k = 3 \)[/tex]: [tex]\( 2 \cdot 3 - 3 = 3 \)[/tex]
- When [tex]\( k = 4 \)[/tex]: [tex]\( 2 \cdot 4 - 3 = 5 \)[/tex]
- When [tex]\( k = 5 \)[/tex]: [tex]\( 2 \cdot 5 - 3 = 7 \)[/tex]
- When [tex]\( k = 6 \)[/tex]: [tex]\( 2 \cdot 6 - 3 = 9 \)[/tex]
Now add these values together:
[tex]\[ -1 + 1 + 3 + 5 + 7 + 9 = 24 \][/tex]
Thus, the first summation component is:
[tex]\[ \sum_{k=1}^6 (2k - 3) = 24 \][/tex]
Multiplying this by 3 gives:
[tex]\[ 3 \sum_{k=1}^6 (2k - 3) = 3 \cdot 24 = 72 \][/tex]
### Step 2: Calculate the Second Summation Component
Next, we consider the second summation:
[tex]\[ \sum_{k=1}^n (4 - 5k) \][/tex]
Substitute [tex]\( n = 6 \)[/tex]:
[tex]\[ \sum_{k=1}^6 (4 - 5k) \][/tex]
Calculate each term inside the summation for [tex]\( k = 1, 2, 3, 4, 5, 6 \)[/tex]:
- When [tex]\( k = 1 \)[/tex]: [tex]\( 4 - 5 \cdot 1 = -1 \)[/tex]
- When [tex]\( k = 2 \)[/tex]: [tex]\( 4 - 5 \cdot 2 = -6 \)[/tex]
- When [tex]\( k = 3 \)[/tex]: [tex]\( 4 - 5 \cdot 3 = -11 \)[/tex]
- When [tex]\( k = 4 \)[/tex]: [tex]\( 4 - 5 \cdot 4 = -16 \)[/tex]
- When [tex]\( k = 5 \)[/tex]: [tex]\( 4 - 5 \cdot 5 = -21 \)[/tex]
- When [tex]\( k = 6 \)[/tex]: [tex]\( 4 - 5 \cdot 6 = -26 \)[/tex]
Now add these values together:
[tex]\[ -1 + (-6) + (-11) + (-16) + (-21) + (-26) = -81 \][/tex]
Thus, the second summation component is:
[tex]\[ \sum_{k=1}^6 (4 - 5k) = -81 \][/tex]
### Step 3: Combine Both Summation Components
Finally, we combine the results of both summations:
[tex]\[ 3 \sum_{k=1}^6 (2k - 3) + \sum_{k=1}^6 (4 - 5k) = 72 + (-81) = -9 \][/tex]
### Final Answer
So, the value of the given summation when [tex]\( n = 6 \)[/tex] is:
[tex]\[ -9 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.